2015
DOI: 10.3892/ol.2015.3129
|View full text |Cite
|
Sign up to set email alerts
|

RACK1 expression contributes to JNK activity, but JNK activity does not enhance RACK1 expression in hepatocellular carcinoma SMMC-7721 cells

Abstract: Abstract.Receptor for activated C kinase 1 (RACK1) is up-regulated in hepatocellular carcinoma (HCC) and has been reported to augment c-Jun N-terminal protein kinase (JNK) activity in HCC SMMC-7721 cells. By contrast, activator protein-1, a downstream JNK transcription factor, has been revealed to mediate the overexpression of RACK1 in melanoma cells. Therefore, the association between RACK1 and JNK activity in HCC cells has yet to be completely elucidated. The present study analyzed the effects of RACK1 or JN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Increasing evidence indicates that RACK1 acts as a versatile signaling pathway hub, providing a platform for protein-protein interaction [10], which plays a crucial role in a diverse number of cellular biological processes, including signal transduction, virus infection, immune response, neural development, and cell differentiation [11,12,13,14]. Emerging studies show that dysregulated RACK1 is supposed to be a biomarker or regulator in a wide spectrum of human cancers [15,16,17,18,19,20,21], which implies that RACK1 could play an important role in genesis and progression [18,22] as well as resistance to chemotherapy in tumors [23]. In addition, Wang et al and Choi et al reported that overexpression of RACK1 strongly was linked with advanced clinical stage and poor prognosis in esophageal squamous cell carcinoma and non-small cell lung cancer [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that RACK1 acts as a versatile signaling pathway hub, providing a platform for protein-protein interaction [10], which plays a crucial role in a diverse number of cellular biological processes, including signal transduction, virus infection, immune response, neural development, and cell differentiation [11,12,13,14]. Emerging studies show that dysregulated RACK1 is supposed to be a biomarker or regulator in a wide spectrum of human cancers [15,16,17,18,19,20,21], which implies that RACK1 could play an important role in genesis and progression [18,22] as well as resistance to chemotherapy in tumors [23]. In addition, Wang et al and Choi et al reported that overexpression of RACK1 strongly was linked with advanced clinical stage and poor prognosis in esophageal squamous cell carcinoma and non-small cell lung cancer [24,25].…”
Section: Introductionmentioning
confidence: 99%